BioID-based Identification of Skp Cullin F-box (SCF)(β-TrCP1/2) E3 Ligase Substrates - Coyaud, Etienne (Mol Cell Proteomics, 2015)
The identification of ubiquitin E3 ligase substrates has been challenging, due in part to low-affinity, transient interactions, the rapid degradation of targets and the inability to identify proteins from poorly soluble cellular compartments. SCF(β-TrCP1) and SCF(β-TrCP2) are well-studied ubiquitin E3 ligases that target substrates for proteasomal degradation, and play important roles in Wnt, Hippo, and NFκB signaling. Combining 26S proteasome inhibitor (MG132) treatment with proximity-dependent biotin labeling (BioID) and semiquantitative mass spectrometry, here we identify SCF(β-TrCP1/2) interacting partners. Based on their enrichment in the presence of MG132, our data identify over 50 new putative SCF(β-TrCP1/2) substrates. We validate 12 of these new substrates and reveal previously unsuspected roles for β-TrCP in the maintenance of nuclear membrane integrity, processing (P)-body turnover and translational control. Together, our data suggest that β-TrCP is an important hub in the cellular stress response. The technique presented here represents a complementary approach to more standard IP-MS methods and should be broadly applicable for the identification of substrates for many ubiquitin E3 ligases.